Radioiodinated N-(2-Diethylaminoethyl)benzamide derivatives with high melanoma uptake: Structure−Affinity Relationships, Metabolic Fate, and Intracellular Localization - Eisenhut, Michael; Hull, William Edmund; Mier, Walter; Gorgas, Karin; Lehmann, Wolf-Dieter; Haberkorn, Uwe (Journal of medicinal chemistry, 2000)
Several radioiodinated N-(dialkylaminoalkyl)benzamides have been used for planar scintigraphy and single-photon emission computed tomography (SPECT) of melanoma metastases. In a quest for improved melanoma uptake and tissue selectivity, structure−activity studies for N-(2-diethylaminoethyl)benzamides with variation of phenyl substituents were performed using C57Bl/6 mice bearing B16 melanoma. Compounds 2 (4-amino-5-bromo-N-(2-diethylaminoethyl)-3-[131I]iodo-2-methoxybenzamide) and 6 (4-acetamido-N-(2-diethylaminoethyl)-5-[131I]iodo-2-methoxybenzamide) showed at 6 h post iv injection, for example, melanoma uptake of 16.6 and 23.2% ID/g, respectively (mean values, n = 3). Uptake was 3−5 times higher (P < 0.01) than observed with benzamides known from the literature and was probably facilitated by the relatively slow urinary excretion of 2 or 6. In contrast, analogues lacking either the MeO, Ac, AcNH, or Br substituents exhibited reduced tumor uptake and high urinary excretion of radioactivity in various benzamide metabolites. Uptake of radioiodinated benzamides in B16 melanoma is not mediated by a specific mechanism such as σ-receptor binding. 2 and 6 exhibited similar melanoma uptake values but quite different σ1-receptor affinities of Ki = 0.278 ± 0.018 and 5.19 ± 0.40 μM, respectively. Uptake studies with IMBA (N-(2-diethylaminoethyl)-3-[131I]iodo-4-methoxybenzamide) or BZA (N-(2-diethylaminoethyl)-4-[131I]iodobenzamide) showed that with increasing dose of unlabeled compound the measured uptake of label was unchanged (IMBA) or even enhanced (BZA) while receptor binding of label decreased. Differential and equilibrium density-gradient centrifugation revealed that most of the radioactivity from labeled IMBA was associated with fractions containing melanin granules. Thus, structure−activity studies indicate that blood clearance rates and metabolic stability are the main determinants for benzamide uptake in melanoma. The high uptake and slow clearance of 6 offer considerable potential for melanoma imaging in patients, and this compound may also prove to be useful for radionuclide therapy.
Gesehen am 09.02.2021